Congruences of the semigroup IO_N (in Ukrainian) - V. O. Pyekhtyeryev; K. S. Trеtyak (Математичні Студії)
We describe congruences of the semigroup IO_N of all order-preserving partial bijections on the set N with the natural order. In particular, we prove that this semigroup contains only one non-Rees congruence.